Determinants and uptake of Hepatitis B virus vaccination among healthcare workers: A Survey in a government-owned teaching hospital Nigeria - Atekoja, Oluwabusolami; Adeniyi, Oluwaseyi; Ladipo, Motunrayo; Omitogun, Olusola; Richard, Adenike; Ogundare, Temilade (KHD-Production, 2025)
Hepatitis B virus (HBV) infection is a primary worldwide health concern, partly due to poor vaccine uptake among healthcare workers who have increased chances of occupational exposure. Nigeria has one of the highest burdens of HBV infection, with an estimated 15% prevalence. Hence, the study objective assessed the determinant and uptake of the Hepatitis B vaccine among Health Care Workers (HCWs) in a Government-owned Teaching Hospital in Ogun State, Nigeria. The study utilized a descriptive cross-sectional design. Samples were determined using Kish Leslie’s formula. Convenience sampling was used to select 124 healthcare workers. Data were collected using a self-administered questionnaire with a reliability of 0.723. Data analysis was done using descriptive, and Pearson Chi-Square and results were presented in tables depicting frequencies and percentages. Findings revealed that 62.9% of HCWs had been vaccinated at least once. However, only 10.5% of respondents were fully vaccinated, indicating a notable gap in the HBV vaccination among the different medical cadres. Factors influencing the uptake rate include vaccine availability (98.4%), distance to vaccination center 74.2%), needle prick (85.5%), HCWs attitude (81.5%), lack of awareness (85.5%), and lack of motivation (87.1%). There was a significant relationship between categories of healthcare workers and uptake of the HBV vaccine (p=0.000). In conclusion, the study calls for concerted efforts from healthcare institutions and policymakers to enforce full vaccination coverage among HCWs to mitigate the burden of Hepatitis B infection in healthcare settings, thus safeguarding the health of both HCWs and the broader community.